2017
DOI: 10.1098/rsob.170058
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase II phosphorylation of cyclin F at serine 621 regulates the Lys48-ubiquitylation E3 ligase activity of the SCF (cyclin F) complex

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder that is characterized by progressive weakness, paralysis and muscle loss often resulting in patient death within 3–5 years of diagnosis. Recently, we identified disease-linked mutations in the CCNF gene, which encodes the cyclin F protein, in cohorts of patients with familial and sporadic ALS and frontotemporal dementia (FTD) (Williams KL et al. 2016 Nat. Commun. 7, 11253. (doi:10.1038/ncomms1125310.1038/ncomms11253)). Cyclin F is a part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 41 publications
0
25
1
Order By: Relevance
“…How does CK2 activity modulate the ubiquitination of SIRT1? Because it has been determined that CK2 phosphorylates E3 ubiquitin ligases such as MDM2 and SCF (cyclin F) complex (28, 29), we speculate that CK2 regulates SIRT1 ubiquitination via CK2-mediated phosphorylation of SIRT1 and/or E3 ubiquitin ligases. Although further studies are required to identify more regulators for SIRT1 ubiquitination, the discovery of CK2 regulation of SIRT1 ubiquitination provides a new avenue of research in the fields of SIRT1 regulation and senescence.…”
Section: Discussionmentioning
confidence: 94%
“…How does CK2 activity modulate the ubiquitination of SIRT1? Because it has been determined that CK2 phosphorylates E3 ubiquitin ligases such as MDM2 and SCF (cyclin F) complex (28, 29), we speculate that CK2 regulates SIRT1 ubiquitination via CK2-mediated phosphorylation of SIRT1 and/or E3 ubiquitin ligases. Although further studies are required to identify more regulators for SIRT1 ubiquitination, the discovery of CK2 regulation of SIRT1 ubiquitination provides a new avenue of research in the fields of SIRT1 regulation and senescence.…”
Section: Discussionmentioning
confidence: 94%
“…It has been suggested that cyclin F is phosphorylated by CKIIα at S621 and S709 to control its activity ( Lee et al., 2017 ). However, the biochemical mechanism of this regulation is unclear, because the S621 residue is far from the F-box motif required for the ubiquitylation activity of cyclin F. We observe that CKIIα interacts with the C-terminal region of cyclin F, which includes the S621 residue.…”
Section: Discussionmentioning
confidence: 99%
“…These findings drive the need to investigate whether TDP-43 is a substrate of the SCF-cyclin F E3 ubiquitin ligase complex. An ALS/FTD-causing pathogenic mutation in cyclin F at amino acid position 621 from serine to glycine (Cyclin F-S621G) was shown to increase the specific ubiquitination at lysine-48 of proteins, which led to the accumulation of lysine-48-ubiquitinated proteins and the impairment of autophagic degradation [199], indicating autophagy to be a degradative mechanism underlying the pathogenesis of ALS/FTD. The roles of cyclin F, which acts as a cyclin as well as an F-box protein, have not been explored in this context, and thus can be further investigated to understand their relevance in mediating neurodegenerative diseases.…”
Section: Cyclin Fmentioning
confidence: 99%